Shielding effectiveness performance of polyaniline-NiFe2O4: Cu composites for sub-8 GHz applications - YUMUŞAK, GÖRKEM (My University, 2023)
Herein, NiFe2O4 doped Cu was synthesized using a mixed-oxide method to investigate its potential for creating composites with high microwave shielding effectiveness. The compound NiFe2−xCuxO4 was synthesized with x values of 0.1, 0.3 and 0.5, respectively. After sintering at 1250°C for 4h, single-phase Ni ferrite was formed. To analyze the phase composition and the structure of the synthesized compound, X-ray diffraction, scanning electron microscopy, and energy-dispersive X-ray spectroscopy were employed. The study\"s findings showed that NiFe2−xCuxO4 did not exhibit a second phase. To create composites with high microwave shielding effectiveness, polyaniline-NiFe2O4:Cu composites were fabricated using a hot-pressing technique, with compositions of NiFe1.9Cu0.1O3.95, NiFe1.7Cu0.3O3.85 and NiFe1.5Cu0.5O3.75 with the aniline, The weight ratios of Cu-added nickel ferrite and aniline were changed from 1:1 to 1:3, and epoxy resin was used. Using a two-port vector network analyzer, the polyaniline-NiFe2O4:Cu composites’ microwave shielding effectiveness performance was examined in the range between 0 and 8GHz. The study found that the shielding effect of the composites could be easily modified by changing the amount of polyaniline present in the specimens for the appropriate frequency bands. At 6.82GHz, using a sample with a thickness of 2.0mm, a minimum shielding effect performance of − 29.74dB was achieved. Overall, the results of this study demonstrate the potential of polyaniline-NiFe2O4:Cu composites as effective microwave shielding materials.
Keywords: Metalurji ve Malzeme Mühendisliği; Malzeme Bilimi ve Mühendisliği; Seramik Malzemeler; Mühendislik ve Teknoloji; Metallurgical and Materials Engineering; Material science and engineering; Ceramic Materials; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Malzeme Bilimi; METALURJİ VE METALURJİ MÜHENDİSLİĞİ; Engineering, Computing & Technology (ENG); MATERIALS SCIENCE; METALLURGY & METALLURGICAL ENGINEERING; Microwave shielding efectiveness; NiFe2O4; Polymer-matrix composite; Polyaniline